2.3 - Limits
2.3 - Limits
2.3 - Limits
3 - LIMITS
PAOLO MANTERO
2.3 - Limits.
Summary from last time. Last class we have seen how to compute the slope
f 0 (a) of the line that is tangent to y = f (x) at x = a (this is called the derivative
of y = f (x) at x = a). To compute the derivative f 0 (a) of a function y = f (x) at a
point x = a, we have basically used the following procedure
(x)
,
Compute m = f (x+x)f
x
0
and then f (a) is obtained by making x become smaller and smaller, until
we set, basically, x = 0.
However, this is just an intuitive definition. To do Mathematics, one cannot just
have intuition, as intuition may be wrong sometimes (and there are many situations
where this is the case), so we need to give a formal definition.
To give you a feeling about how hard it can be to formalize intuitive ideas, we
first study this apparently unrelated question. However, an answer to this question
gives us an idea of the difficulties in defining a limit and how to overcome them.
Here is the baby question.
Question
1. How can we say in mathematical language that x tends to become
Example
2. Give a formal mathematical sentence stating that x tends to become
Sol.
What we would like to express is that y = x can get arbitrarily close
pick any small number, say , then we can make the difference between x and 2
become smaller than this tiny value . This becomes
| x 2| < .
Now, let us work out the second half of the sentence, namely, by choosing values
of x that are closer and closer to x = 2. We translate it by saying that there exists
Date: January 13, 2014.
1
PAOLO MANTERO
a small number > 0 such that |x 2| < . Putting the two sentences together we
have
for every > 0, there exists > 0 s.t. | x 2| < for every x with |x 2| < .
Definition 3. The limit of a function y = f (x) at a point x = a is L, if
for every > 0, there exists > 0 such that |f (x)L| < for every x with |xa| < .
We write it limxa f (x) = L.
Note: there is usually one problem in the midterm asking to prove that a
certain limit is a given number L using the definition of limit. So, pay special
attention to the next examples!
With this new language, we can check that limx2 (x + 3) = 5.
Example 4. Prove that limx2 (x + 3) = 5 using the definition of limit.
Sol. Choose an > 0, we need to find > 0 so that |(x + 3) 5| < for all x
with |x 2| < .
Preliminary Analysis. We want to find a number > 0 so that
if |x 2| <
then |x 2| <
x2
Let us see another couple of examples.
Example 5. Prove that limx1 (2x 9) = 7 using the definition of limit.
Sol. Choose an > 0, we need to find > 0 so that |(2x 9) (7)| < for all
x with |x 1| < .
Preliminary Analysis. We want to find a number > 0 so that
if |x 1| <
Dont forget to put the parenthesis around the (7) (if you do not do it, you will
get a wrong answer!)
We simplify the inequality involving , indeed, we have
(2x 9) (7) = 2x 9 + 7 = 2x 2 = 2(x 1).
Then, we need a > 0 such that
if |x 1| <
We can work out the second inequality, to make it look similar to the first one:
|2(x 1)| <
2|x 1| <
|x 1| <
2
Now, it looks similar to the first one:
if |x 1| < then |x 1| <
2
The reason for doing so is that now, an immediate comparison suggests that we
should choose = 2 . However, we still need to check it!
Proof (showing that this works). Given > 0, choose = 2 . if |x 1| < ,
then
|(2x 9) (7)| = |2x 2| = 2|x 1| is < 2 = 2 = .
2
Thus, we have proved that
if |x 1| <
x1
Example 6. Prove that limx1 (7x + 3) = 4 using the definition of limit.
Sol. Choose an > 0, we need to find > 0 so that |(7x + 3) (4)| < for all
x with |x (1)| < .
Preliminary Analysis. We want to find a number > 0 so that
if |x (1)| <
Dont forget to put the parenthesis around the (1) and (4) (if you do not do it,
you will get a wrong answer!)
We simplify the first inequality to obtain
|x (1)| <
becomes
|x + 1| < .
As before, we now work out the second inequality to make it look similar to the
first one:
|7(x + 1)| <
7|x + 1| <
|x + 1| <
7
PAOLO MANTERO
then |x + 1| <
x1
More in general, we can use the definition of limit to prove (similarly to the
above) that
lim x = a.
xa
x2
x2
x2
Actually, this is a (more) general rule!
Theorem 8. (The limit of a product is the product of the limits)
If limxa f (x) = L and limxa g(x) = M , then
lim f (x) g(x) = L M.
xa
The above theorem is the first Limit Law, sometimes called the Product Law.
Example 9. Compute limx1 x3 .
x1
x1
There are several similar Limit Laws, that are useful to avoid the - computations. Let us see a few of them:
Theorem 10. (Limit Laws)
If limxa f (x) = L and limxa g(x) = M , then
(Product Law) limxa f (x) g(x) = L M .
(x)
L
(Quotient Law) limxa fg(x)
=M
(if M 6= 0)
(Sum Law) limxa f (x) + g(x) = L + M .
(Difference Law) limxa f (x) g(x) = L M .
(Scalar Law) limxa k f (x) = k L, for any number k.
Example 11. Compute limx3
x2 2x+1
x5 .
L
Sol. By the Quotient Law, the answer is M
, where L = limx2 x2 2x + 1 and
M = limx3 x 5. By Sum and Product Laws,
x3
x3
x3
Therefore
L
4
x2 2x + 1
=
=
= 2.
x3
x5
M
2
lim
Example 12. Compute limx2
5x8
x2 1 .
L
Sol. By the Quotient Law, the answer is M
, where L = limx2 ((5x 8) and
2
M = limx2 (x 1). By Sum and Product Laws,
x2
Therefore
x2
x2
5x 8
L
18
=
=
= 6.
2
x2 x 1
M
3
lim
IMPORTANT: It is often useful to plug in the value x = a to determine
the limit.
2
For instance, to compute limx3 x 2x+1
x5 , we could have also just plugged in x = 3
and obtained
32 2(3) + 1
96+1
=
= 2.
35
2
PAOLO MANTERO
2h+h2
.
h
Sol. If we use the Quotient Law directly, we are in trouble, because the numerator gives (by Product and Sum Laws)
lim 2h + h2 = 0.
h0
h0
2h + h2
h(2 + h)
= lim
= lim 2 + h
h0
h0
h0
h
h
which is 2 by the Sum Law.
lim
0
0,
t2 4
t2 +3t10 .
2
2 4
44
Sol. If we plug in t = 2 we obtain 22 +3(2)10
= 4+610
= 00 . This is of course
not a number, hence it is not an acceptable answer. By the above, we know that
we need to factor out something. For the numerator of the fraction, we can either
use the quadratic formula, or realize it is a difference of squares. In either way we
have t2 4 = (t 2)(t + 2).
For the denominator, we employ the quadratic formula or intuition (or any other
method you may know). In any case, we should obtain t2 + 3t 10 = (t 2)(t + 5).
Hence
t2 4
(t 2)(t + 2)
t+2
2+2
4
lim 2
= lim
= lim
=
= .
t2 t + 3t 10
t2 (t 2)(t + 5)
t2 t + 5
2+5
7
Hence, we first simplified the common factor of numerator and denominator, and
then we could plug in t = 2.
t3 9t
t2 +4t+3 .
3
(3) 9(3)
27+27
0
Sol. If we plug in t = 3 we obtain (3)
2 +4(3)+3 = 912+3 = 0 . This is of
course not a number, hence it is not an acceptable answer. By the above, we know
that we need to factor out something. For the numerator of the fraction, we can
first factor out a t, to obtain t3 9t = t(t2 9), and then either use the quadratic
formula, or realize the second factor is a difference of squares. In either way we
have
t3 9t = t(t2 9) = t(t 3)(t + 3).
For the denominator, we employ the quadratic formula or intuition (or any other
method you may know). In any case, we should obtain t2 + 4t + 3 = (t + 1)(t + 3).
Hence
t3 9t
t(t 3)(t + 3)
t(t 3)
lim 2
= lim
= lim
t3 t + 4t + 3
t3 (t + 1)(t + 3)
t3 t + 1
now we plug in t = 3 and obtain
t(t 3)
(3)(3 3)
18
lim
=
=
= 9.
t3 t + 1
3 + 1
2
SURGE 233, Department of Mathematics, University of California at Riverside,
Riverside, CA 92521
E-mail address: [email protected]